A review on Latvian Historical Building Stock with Heavy Walls. (September 2016) - Blumberga, Andra; Kass, Kristaps; Kamendere, Edite
Abstract: The conservation of historic buildings' cultural values and the improvement of their energy performance can be perceived as rather contradictory. A thermal insulation cannot always be applied on the exterior surface of external walls. In that case, interior insulation measures should be investigated and currently represent the most difficult retrofit measure in historic buildings. The main objective of this study is to carry out literature review and to examine most commonly found historic building heavy wall types in Latvia, determine their physical properties, classify them by different types, observe and describe main historic building envelope deterioration symptoms and their possible causes. The study shows that historical buildings consume one third of total final heating energy consumed by both residential and non-residential building sector. The study also reveals that historical building external wall hygrothermal properties have not been widely studied in Latvia. This study will serve as basis for development of effective, comprehensive decision guidelines to improve the energy performance of historic buildings by investigating interior insulation measures.